Дикая собака Динго, или повесть о первой любви - Фраерман Руфим Исаевич (Школьная библиотека, 2017)
Экземпляры: (20210913) / Инвентарный номер: 41879 / Цена: 152.00 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Ф 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=411.2)6